11C-4DST PET/CT Imaging of Cardiac Sarcoidosis: Comparison With 18F-FDG and Cardiac MRI. (June 2018) - Hotta, Masatoshi; Minamimoto, Ryogo; Kubota, Shuji; Awaya, Toru; Hiroi, Yukio
Abstract : Abstract: A 75-year-old woman with a history of sarcoidosis presenting with low cardiac output and complete right bundle-branch block underwent 4′-[methyl- 11 C]-thiothymidine (4DST) PET/CT after cardiac MRI and FDG PET/CT for the evaluation of suspected cardiac sarcoidosis (CS) before treatment. Cardiac MRI revealed late gadolinium enhancement on the anterior-to-lateral and posterior wall, indicating CS. FDG uptake was shown on the anterior-to-lateral wall, but not on the posterior wall. In contrast, 4DST uptake was demonstrated on both anterior-to-lateral and posterior walls. Use of 4DST appears promising for detecting CS without dietary restriction, due to the lack of physiological uptake in myocardium.